Damage and risk assessment for reinforced concrete wall panels subjected to explosive blast loading - Shi, Yufeng; Stewart, Mark G. (International journal of impact engineering, 2015)
The structural integrity of reinforced concrete (RC) structures in blast events is important for critical facilities. In this paper, a structural reliability analysis is conducted to predict the damage and risk reduction for RC wall panels subjected to explosive blast loading. Due to considerable uncertainties associated with material properties, dimensions, structural response, blast loading, as well as expected damage, probabilistic methods are used in quantifying the probability of damage for conventional and blast-resistant RC precast cladding wall panels by incorporating spatial and non-spatial variables. The variability of blast loading is also taken into consideration. Monte Carlo simulation and numerical methods are utilized to predict damage of RC wall panels subject to various threat scenarios, based on a physics-based computer programme LS-DYNA to estimate maximum support rotations. It was found that spatial variability of concrete compressive strength and concrete cover has little effects on the structural reliability for precast concrete panels, and the blast-resistant wall has 5%–100% lower probability of hazardous failure than the corresponding value for a conventional wall. •An approach is presented to estimate the probability of damage of RC wall panels subject to explosive blast loading.•Spatial variability of material and dimensional properties are considered.•The effect of blast load variability on structural reliability is investigated.•Monte Carlo simulation is used to derive blast reliability curves.